(untitled) (TAJ: Journal of Teachers Association, 2023)
Background: The mental foramen is an important anatomical landmarks during surgical intervention and anaesthetic nerve block procedure involving inferior alveolar nerve and mental nerve. Objectives: The aim of this study was to determine the variation of position of mental foramen in relation to side and sex. Methods: This cross-sectional type of descriptive study was conducted over a period of 1 year from January 2021 to December 2021 in the Department of Anatomy, Rajshahi Medical College, Rajshahi. This study was performed on 250 dry adult human mandibles (148 were male and 102 were female mandibles) which were collected from the students of Department of Anatomy, Rajshahi Medical College, Rajshahi as well as other Medical Colleges after fulfilling the inclusion criteria. Data were collected purposively with the help of a semi-structured questionnaire. All the measurements were performed using digital sliding Vernier calipers and the data were analyzed via SPSS software, version 24.0. Statistical significance was evaluated as appropriate probability level p < 0.05 for all tests. Results: The study revealed that 96% of mental foramens were oval in shape. Out of six morphometric parameters of mental foramen, four parameters (Distance from alveolar crest to upper margin, distance from lower border of mandible to lower margin, distance from symphysis menti to medial margin and horizontal diameter of mental foramen) were not statistically significant (p > 0.05) but distance from posterior border of ramus of mandible to lateral margin and vertical diameter of mental foramen were statistically significant (p < 0.001). Horizontal diameter of mental foramen of right halves and vertical diameter of mental foramen of both halves were higher in male than female and these were statistically significant (p < 0.05). But horizontal diameter of mental foramen of left halves between male and female was statistically non-significant (p > 0.05). Conclusion: This study might help us in establishing a reference data-base in our country for the Anatomists in general, Dental Surgeons and Maxillofacial Surgeons. TAJ 2023; 36: No-2: 193-200